2009
DOI: 10.1118/1.3101820
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific finite element modeling of respiratory lung motion using 4D CT image data

Abstract: Development and optimization of methods for adequately accounting for respiratory motion in radiation therapy of thoracic tumors require detailed knowledge of respiratory dynamics and its impact on corresponding dose distributions. Thus, computer aided modeling and simulation of respiratory motion have become increasingly important. In this article a biophysical approach for modeling respiratory lung motion is described: Major aspects of the process of lung ventilation are formulated as a contact problem of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 68 publications
7
117
2
2
Order By: Relevance
“…In an extension of this work, Didier et al 39 used the same FEM model and investigated the kinematic effects of the ribs on the motion during a breathing cycle by using a finite helical axis ͑FHA͒ method. Extending the work of Zhang et al, 37 Werner et al 34,45 recently proposed a respiratory lung motion model incorporating contact mechanics. Instead of using contact elements, an augmented Lagrangian algorithm was used for the contact formulation in the FEM software COMSOL MULTIPHYSICS ͑COMSOL AB, Sweden͒.…”
Section: Introductionmentioning
confidence: 99%
“…In an extension of this work, Didier et al 39 used the same FEM model and investigated the kinematic effects of the ribs on the motion during a breathing cycle by using a finite helical axis ͑FHA͒ method. Extending the work of Zhang et al, 37 Werner et al 34,45 recently proposed a respiratory lung motion model incorporating contact mechanics. Instead of using contact elements, an augmented Lagrangian algorithm was used for the contact formulation in the FEM software COMSOL MULTIPHYSICS ͑COMSOL AB, Sweden͒.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters for lung tissue elasticity and poroelasticity have been proposed [34,5,35,10,36], although there is no consensus in the values in the literature. In this study, we have chosen parameters as shown in Table 1 …”
Section: Simulation Parametersmentioning
confidence: 99%
“…In this work, we focus on the link between tissue deformation and ventilation. Previous work of whole organ lung models has typically focused on modelling either ventilation or tissue deformation [1,2,3,4,5,6,7,8]. However, the two components are intrinsically linked; evaluating them separately does not necessarily provide an accurate description of lung function.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially the case when two objects slip along each other, which can be observed for example in the case of lung- [4] or liver motion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Arising discontinuities at object boundaries are addressed by several approaches: In [4] finite element methods are used in order to simulate the physiology of respiration dynamics, point-and surface-based registration approaches are used in [6]. While these allow to explicitly or implicitly incorporate boundary conditions, inner-organ information like bronchial or vessel trees are dismissed which results in an inaccurate registration of those structures.…”
Section: Introductionmentioning
confidence: 99%